Immunogenic characteristics of microsatellite instability‐low esophagogastric junction adenocarcinoma based on clinicopathological, molecular, immunological and survival analyses. Issue 5 (10th October 2020) - Imamura, Yu; Toihata, Tasuku; Haraguchi, Ikumi; Ogata, Yoko; Takamatsu, Manabu; Kuchiba, Aya; Tanaka, Norio; Gotoh, Osamu; Mori, Seiichi; Nakashima, Yuichiro; Oki, Eiji; Mori, Masaki; et al.
Abstract: Microsatellite instability (MSI) is categorized by mutation frequency: high MSI (MSI‐H), low MSI (MSI‐L) and microsatellite stable (MSS). MSI‐H tumors have a distinct immunogenic phenotype, with immunotherapies using checkpoint inhibitors already approved for the treatment of MSI‐H gastroesophageal adenocarcinoma (GEA); this is not observed for MSI‐L or MSS. Here, we tested the hypothesis that MSI‐L tumors are also a distinct phenotype and potentially immunogenic. MSI‐PCR assays (BAT25, BAT26, BAT40, D2S123, D5S346 and D17S250) were performed on 363 Epstein‐Barr virus‐negative, surgically resected esophagogastric junction (EGJ) adenocarcinoma samples. Tumors were characterized as MSI‐H (≥2 markers), MSI‐L (1 marker) or MSS (0 markers). CD8+ cell counts, PD‐L1 and HER2 expression levels, TP53 mutations, epigenetic alterations and prognostic significance were also examined. All pathological and molecular experiments were conducted using serial, whole‐tumor sections of chemo‐naïve surgical specimens. MSI‐H and MSI‐L were assigned to 28 (7.7%) and 24 (6.6%) cases, respectively. Compared to MSS cases, MSI‐L cases had significantly higher intratumoral CD8+ cell infiltration ( P = .048) and favorable EGJ cancer‐specific survival (multivariate hazard ratio = 0.35, 95% CI, 0.12‐0.82; P = .012). MSI‐L tumors were also significantly associated with TP53 ‐truncating mutations as compared to MSI‐H ( P = .009) and MSS ( P = .012) cases, and this trend was also observed in GEA data from The Cancer Genome Atlas (TCGA). Indel mutational burden among TCGA MSI‐L tumors was significantly higher than that of MSS tumors ( P = .016). These results suggest that MSI‐L tumors may have a distinct tumor phenotype and be potentially immunogenic in EGJ adenocarcinoma. Abstract : What's new? Gastroesophageal adenocarcinoma patients with high microsatellite instability tumors present with a distinct phenotype and good response to immunotherapy. However, little is known about the immunogenic phenotype of low microsatellite instability (MSI‐L) tumors. Here, the authors show that, compared to gastroesophageal adenocarcinoma microsatellite stable tumors, MSI‐L tumors have significantly higher indel mutational burden, higher levels of intratumoral CD8+ cell infiltration, and favorable outcomes. The findings suggest a distinct immunogenic phenotype for MSI‐L tumors and the potential to also treat this gastroesophageal adenocarcinoma subtype by immunotherapy.